A brief summary of loxapine inhalation for rapid tranquillisation: what is its place in practice?. (22nd October 2013) - Parker, Caroline
Abstract Loxapine has recently been licensed in the UK for the management of mild-to-moderate agitation in adults with schizophrenia or bipolar affective disorder. Loxapine is a first generation antipsychotic, and although not previously available in the UK, it has been used orally and as an intramuscular injection in some countries for many years. It is now formulated in a single use inhalator. This is the first newly licensed medicine in the UK for the management of agitation for over five years. This brief article provides an overview of this new medicine in order to help readers consider its place in regular clinical practice prior to its UK launch.